(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The global outbreak generated by the pandemic (COVID-19) has disrupted countless aspects of society. In Colombia, the education sector was seriously affected. Educational institutions had to quickly adapt to distance education, using Information and Communication Technologies (ICT) as a key tool, especially in initial education. This article examines teachers’ experiences of incorporating ICT into this level of education during the pandemic. The transition from an in-person to a virtual educational environment has raised important questions in terms of equity, privacy, educational quality, and student well-being. At the same time, it has opened the door to new forms of teaching and learning that deserve to be explored and made the most of.